Studi Ekologi Variabel Cuaca terhadap Kejadian Campak di Kota Tanjungpinang Tahun 2013-2017 - Indra Martias; Rinaldi Daswito (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Measles is a highly contagious disease, the main cause of child mortality and is still a global pro-blem, including in Indonesia. During the period of 2015-2017, there were 129 cases of measles in Tanjungpinang City. Several studies had shown that there was a relationship between weather variables and the incidence of measles. This study aimed to determine the pattern of immuni-zation coverage, population density and weather variables (rainfall, air humidity, air temperature, and wind speed) on measles cases in Tanjungpinang City in 2010-2017. The study design was an ecological study with a spatial-temporal approach. The unit of analysis was a group of indi-viduals (aggregate) measuring exposure/risk factors for disease events by considering temporal factors or time at the population level. The study population is the administrative area of ??Tan-jungpinang City with the incidence of measles sufferers during the period 2010-2017. The data used were secondary data from related agencies. There was a relationship between the vari-ables of rainfall and air humidity with the incidence of measles per year in Tanjungpinang City in the period 2010-2017. While the variable average air temperature, minimum air temperature, maximum air temperature, and wind speed, were not related to the incidence of measles. Dis-trict/City or Provincial Health Offices need to use weather variable data in terms of surveillance measures for measles for mitigation and early vigilance towards increased incidence of measles, especially during the rainy season each year.